2020
DOI: 10.1097/md.0000000000023271
|View full text |Cite
|
Sign up to set email alerts
|

The clinical profiles, management, and prognostic factors of biliary mixed neuroendocrine nonneuroendocrine neoplasms

Abstract: Background: Mixed neuroendocrine nonneuroendocrine neoplasms (MiNENs) originating from the biliary system (gallbladder, biliary tract, or ampulla of Vater) are extremely rare and have not been discussed in detail or systematically. We aimed to present the demographics, clinicopathological characteristics, management, and prognostic factors of biliary MiNENs. Methods: A systematic search of electronic biomedical databases (Web of Science, PUBMED, and Embase) was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 50 publications
(3 reference statements)
0
12
0
Order By: Relevance
“…Due to the few numbers of cases and their heterogeneity, the standard treatment for MINEN, especially involving adjuvant therapy, is still controversial. In their systematic review of biliary MINEN, Wen et al reported that incomplete resection, Ki-67 index (≥ 50), tumor stage, NEC grade, and non-NEC grade were prognostic factors for poor overall survival, and that adjuvant chemoradiotherapy for those patients may contribute to better overall survival [ 8 ]. Yoshimachi et al also reported in their literature review of ampullary MANEC that multidisciplinary treatment including chemotherapy may improve the prognosis of patients with MANEC [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the few numbers of cases and their heterogeneity, the standard treatment for MINEN, especially involving adjuvant therapy, is still controversial. In their systematic review of biliary MINEN, Wen et al reported that incomplete resection, Ki-67 index (≥ 50), tumor stage, NEC grade, and non-NEC grade were prognostic factors for poor overall survival, and that adjuvant chemoradiotherapy for those patients may contribute to better overall survival [ 8 ]. Yoshimachi et al also reported in their literature review of ampullary MANEC that multidisciplinary treatment including chemotherapy may improve the prognosis of patients with MANEC [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature review reported by Yoshimachi et al, seven out of 15 cases of ampullary MINEN received adjuvant chemotherapy (oxaliplatin-based combination chemotherapy; n = 5, S-1; n = 2) [ 9 ]. In addition, Wen et al reported that 22 out of 51 patients with biliary MINEN received adjuvant chemotherapy, and 21 of 22 received platinum-based combination therapy [ 8 ]. Thus, platinum-based combination therapy is likely to be the mainstream adjuvant chemotherapy for MINEN following radical resection.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MiNEN with predominant NEC components are more likely to metastasize to LNs [ 3 ]. Several authors reported that patients with resectable cases of MiNEN who underwent complete surgical resection had overall better prognosis [ 2 , 8 , 9 ]. Chen et al [ 1 ] described the aggressive nature of the gallbladder NEC, and reported that patients with NEC had significantly higher rate of LN metastases and poorer prognosis, when compared to patients with gallbladder adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although each component of MiNEN must account for at least 30% of the whole neoplasm to meet the criteria for MiNEN, several authors suggested that the prognosis was influenced by the most aggressive histological components, regardless of the percentage of those components [ 8 , 9 , 15 ]. Our patient had less than 30% of NEC components, who did not meet the criteria for MiNEN, but presented with diffusely metastatic LNs with NEC components.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systemic review based on 53 studies to predict the clinicopathological features and prognosis of biliary MiNENs, including gallbladder MiNENs, showed a median overall survival time of 21 mo. In addition, radical resection and small morphological subtype were independent prognostic factors associated with higher overall survival, and radical resection (R0) and younger age (< 65 years) were associated with higher recurrence-free survival time[ 115 ].…”
Section: Organ-specific Clinicopathological Findingsmentioning
confidence: 99%